A Scoping Review of Augmented/Virtual Reality Health and Wellbeing Interventions for Older Adults: Redefining Immersive Virtual Reality - Carroll, Joanne; Hopper, Louise; Farrelly, Aaron Mark; Lombard-Vance, Richard; Bamidis, Panagiotis D.; Konstantinidis, Evdokimos I. (Frontiers in Virtual Reality, 2021)
Augmented and virtual reality (AR/VR) technologies are regularly used in psychology research to complement psychological interventions and to enable an individual to feel as if they are in an environment other than that of their immediate surroundings. A scoping review was performed to identify how AR/VR was being used with older adult populations to impact their physical and mental health. The review also sought to determine whether the terminology used in AR/VR research was consistent. The results show that 65 studies have been published in the last 20-years that meet the inclusion criteria (virtual/augmented reality) technology to impact older adults’ physical/mental health and wellbeing. Participants included healthy, physically and cognitively impaired, and emotionally vulnerable older adults. We argue that over 70% of the studies included in this review were mislabelled as VR and only six papers included fully immersive VR/AR. The remaining studies use less immersive variants of virtual reality with their populations, and only one study made use of AR, which prompted the suggestion of a new definition for virtual reality. This paper also calls for an updated taxonomy of augmented and virtual reality definitions to address the lack of consistency found in studies that identify themselves as AR/VR when they are using less immersive technical set-ups, including displaying non-interactive videos on 2D screens.